2022
DOI: 10.3390/nano12203612
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Electrolytes for Lithium–Sulfur Batteries: Challenges, Progress, and Strategies

Abstract: Lithium–sulfur batteries (LSBs) represent a promising next-generation energy storage system, with advantages such as high specific capacity (1675 mAh g−1), abundant resources, low price, and ecological friendliness. During the application of liquid electrolytes, the flammability of organic electrolytes, and the dissolution/shuttle of polysulfide seriously damage the safety and the cycle life of lithium–sulfur batteries. Replacing a liquid electrolyte with a solid one is a good solution, while the higher mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Moreover, the shuttle of lithium polysulfides could be avoided when ISEs [154] are used, and sulfide-based SEs are the most promising ISEs for LiÀ S batteries due to their high ionic conductivity and compatibility with sulfur. However, they are not stable against metallic Li.…”
Section: Pouch-type Li-s and Lià O 2 Solid-state Lmbsmentioning
confidence: 99%
“…Moreover, the shuttle of lithium polysulfides could be avoided when ISEs [154] are used, and sulfide-based SEs are the most promising ISEs for LiÀ S batteries due to their high ionic conductivity and compatibility with sulfur. However, they are not stable against metallic Li.…”
Section: Pouch-type Li-s and Lià O 2 Solid-state Lmbsmentioning
confidence: 99%
“…The long-chain polysulfides at the anode are then semi-permanently reduced into insoluble Li 2 S. The consequences are (a) reduced active material, which decreases capacity; (b) decreased Li-ion diffusion due to a build-up of non-reactive LiPSs; (c) large volume expansion that may break the enclosed LSB; and (d) fast self-discharging that makes commercialization difficult. While using solid-state electrolytes can effectively prevent the shuttle effect, LSBs with even the latest solid-state electrolytes are not commercially viable due to poor ionic conductivity and slow redox kinetics that limit energy storage and power density [ 31 , 32 , 33 ]. Thus, there have been great efforts to mitigate the shuttle effect using novel NF separators in liquid electrolytes.…”
Section: Lithium Polysulfide Shuttle Effectmentioning
confidence: 99%
“…Recently, it has been revealed that the solvation of polysulfides in the electrolyte is associated with the reaction pathway of sulfur. Electrolytes are hereby classified into three groups depending on the solubility of polysulfides (including sparingly, moderately, and highly solvating systems) [ 49 ] while they can be alternatively categorized into liquid, [ 50 ] gel‐polymer, [ 51 ] and solid‐state [ 52 ] types by physical states.…”
Section: Challenges Of Lithium–sulfur Batteriesmentioning
confidence: 99%